Acute Toxicity and Allergy Test of Pegagan Leaf Extract (Centella asiatica) on Mice (Mus muscullus) - Hendri Poernomo; Mochammad Taha Ma'aruf; Luh Gede Pradnyani (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Gotu kola (Centella asiatica) is a type of plant that is often used as a traditional medicine that has the properties to accelerate wound healing, rheumatic inflammation, asthma, hemorrhoids, dysentery, fever, and as a blood enhancer. The use of plants as medicinal raw materials is increasing, so it is necessary to prove its safety by conducting acute toxicity tests and allergy tests. Material and Method: in vivo laboratory experiment with quasi experimental method and post test-Only Control Group Design with histopathological observations on the liver of mice. Mice will be grouped into 5 groups and each group consists of 5 mice consisting of 1 control group and 4 treatment groups. The treatment group was given gotu kola leaf extract orally and observations were made for 14 days. Result and Discussion: obtained the results of acute toxicity test research, obtained LD50 value is 12.5gr/kg BW (mild toxic), on microscopic observation in the control group there was no damage to the liver, while in the treatment group there were changes in the form of liver damage. For acute toxicity, the weight of mice after being given gotu kola leaf extract was tested using Shapiro Wilk and Kruskal Wallis tests. From the analysis results, there was no significant difference. Conclusion: Gotu kola leaf extract does not cause toxic effects on mice mortality and also does not cause allergies in mice.